Advances in cotton harvesting aids - Xie, Zhangshu; Xie, Xuefang; Qin, Yeling; Yang, Dan; Zhou, Zhonghua; Wang, Qiming; Liu, Aiyu; Tu, Xiaoju (Frontiers in Plant Science, 2025)
During the cotton harvesting stage, the application of chemical harvest aids, such as thidiazuron and ethephon, facilitates cotton defoliation and boll maturation, serving as a crucial management tool in modern cotton cultivation systems. This paper reviews recent advancements in cotton defoliation and ripening research; delves into the physiological mechanisms underlying defoliation, boll maturation, and cotton fiber development; and summarizes the effects of major defoliants and herbicide-type desiccants on plants. It also explores the roles of hormones and genes that are involved in the defoliation process and identifies the key factors influencing the effectiveness of harvest aids. Additionally, this paper offers recommendations and scientific prospects for optimizing cotton defoliation and ripening technologies in the future. Through these contributions, it aims to provide valuable insights for the research and application of efficient harvesting of mature cotton, stimulate innovation in cotton defoliation and ripening technologies, enhance the quality and yield of cotton, reduce labor costs, and contribute to the sustainable development of the cotton industry.